Ultrasound-engineered synthesis of WS2@CeO2 heterostructure for sonocatalytic degradation of tylosin - Tizhoosh, Negar Yousef; Khataee, Alireza; Hassandoost, Ramin; Soltani, Reza Darvishi Cheshmeh; Doustkhah, Esmail (Elsevier, 2020)
The main aim of the present investigation was the intercalation of WS2 nanosheets in the structure of ceria (CeO2) to be used for the efficient catalytic destruction of tylosin (TYL) as a macrolide antibiotic in water. Assynthesized heterostructured catalyst was placed in a sono-reactor (40 kHz and 300 W) in order to degrade TYL through the sonocatalysis. 15 wt% WS2/CeO2 was chosen for performing the systematic experiments. Decreasing the concentration of TYL, along with increasing the WS2/CeO2 dosage led to reduced degradation efficiency. The water hardness was demonstrated to be a suppressive agent on the sonocatalysis of the target pollutant. As-generated holes, (OH)-O-center dot, and also O-2(center dot-) were responsible for the degradation of TYL. Increasing the ultrasound power and operating temperature enhanced the degradation efficiency. The degradation rate boosted up when the temperature was raised from 10 degrees C (0.0107 1/min) to 40 degrees C (0.0165 1/min). Moreover, the lowest activation energy (E-a) for sonocatalytic degradation was obtained as 10.81 kJ/mol. The sonocatalytic activity of WS2/CeO2 in the sono-reactor encountered insignificant change within five consecutive operational runs (similar to 15% reduction). The mechanism and pathways of the sonocatalytic decomposition of TYL are also proposed.
Keywords: Sonocatalysis; Heterostructured sonocatalyst; Macrolide antibiotic; Advanced water treatment; Tylosin; Antibiotic degradation